Course notes : equity and trusts - Barnett, Simon (New York : Routledge, 2014)
'Course Notes is designed to help you succeed in your law examinations and assessments. Each guide supports revision of an undergraduate and conversion GDL/CPE law degree module by demonstrating good practice in creating and maintaining ideal notes. Course Notes will support you in actively and effectively learning the material by guiding you through the demands of compiling the information you need. - Written by expert lecturers who understand your needs with examination requirements in mind - Covers key cases, legislation and principles clearly and concisely so you can recall information confidently - Contains easy to use diagrams, definition boxes and work points to help you understand difficult concepts - Provides self test opportunities throughout for you to check your understanding - Illustrates how to compile the ideal set of revision notes - Covers the essential modules of study for undergraduate llb and conversion-to-law GDL/CPE courses - Additional online revision guidance such as sample essay plans, interactive quizzes and a glossary of legal terms at www.unlockingthelaw.co.uk'--
Includes bibliographical references and index.
Keywords: Equity -- United Kingdom; Trusts and trustees -- United Kingdom